Genome-wide DNA methylation and transcription analysis reveal the potential epigenetic mechanism of heat stress response in the sea cucumber Apostichopus japonicus - Chang, Mengyang; Ge, Jianlong; Liao, Meijie; Rong, Xiaojun; Wang, Yingeng; Li, Bin; Li, Xinrong; Wang, Jinjin; Zhang, Zheng; Yu, Yongxiang; Wang, Chunyuan (Frontiers in Marine Science, 2023)
DNA methylation is an important epigenetic modification that regulates many biological processes. The sea cucumber Apostichopus japonicus often suffers from heat stress that affects its growth and leads to significant economic losses. In this study, the mRNA expression patterns and DNA methylation characteristics in the body wall of A. japonicus under heat stress were analyzed by whole-genome bisulfite sequencing (WGBS) and transcriptome sequencing (RNA-seq). We found that CpG was the main DNA methylation type, and heat stress caused a significant increase in the overall methylation level and methylation rate, especially in the intergenic region of the A. japonicus genome. In total, 1,409 differentially expressed genes (DEGs) and 17,927 differentially methylated genes (DMGs) were obtained by RNA-seq and WGBS, respectively. Association analysis between DNA methylation and transcription identified 569 negatively correlated genes in both DMGs and DEGs, which indicated that DNA methylation affects on transcriptional regulation in response to heat stress. These negatively correlated genes were significantly enriched in pathways related to energy metabolism and immunoregulation, such as the thyroid hormone signaling pathway, renin secretion, notch signaling pathway and microRNAs in cancer. In addition, potential key genes, including heat shock protein (hsp70), calcium-activated chloride channel regulator 1(clca1), and tenascin R (tnr), were obtained and their expression and methylation were preliminarily verified. The results provide a new perspective for epigenetic and transcriptomic studies of A. japonicus response to heat stress, and provide a reference for breeding sea cucumbers resistant to high temperatures.